Strategi Menghindarkan Indonesia dari Ancaman Resesi Ekonomi di Masa Pandemi - Blandina, Selena; Noor Fitrian, Alvin; Septiyani, Wulan (Efektor, 2020)
The Covid-19 pandemic has hit the world, especially the State of Indonesia. The Covid-19 pandemic not only had an impact on increasing casualties but also had a broad and direct impact on the decline in the world economy. Data from the Central Statistics Agency reported that Indonesia's economic growth contracted by 5.32% in the second quarter of 2020. Then in the first quarter, it contracted by 6.13%, which was the worst record for the economy since 1999. Predictions that the global economy will enter a recession that very sharp until the end of the first quarter of 2020 has been informed by the International Monetary Fund and the World Bank. This study aims to analyze strategies that can be taken by Indonesia in facing the threat of an economic recession. The research method used is descriptive qualitative, where the data is obtained from an in-depth, analyzed literature study. The results of this study obtained strategies for the Indonesian government to face the threat of recession, including the government's fiscal and monetary capabilities, productivity improvements, competitiveness; investigation; and the world economy. In addition to the role of the government, the community also has a role to play, such as developing startup business innovations and supporting UMKM business players in an effort to encourage economic growth to keep going amid the economic crisis caused by the Covid-19 outbreak.